Pengaruh Beban Kerja, Etika Profesional, Knowledge Dan Burnout Terhadap Kinerja Auditor Kantor Akuntan Publik Di Jakarta - Taruli Elisabeth Hutabarat; Y. Agus Bagus Budi N (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research is conducted to examine the influence of workload, professional ethics, knowledge, and burnout on the audit performance of auditors working in Public Accounting Firms (KAP) in Jakarta. The data collection method employed in this study utilized questionnaires distributed to 200 external auditors working in Public Accounting Firms (KAP) in Jakarta. The data analysis method used in this research is Partial Least Square. The results indicate that workload, professional ethics, knowledge, and burnout significantly affect the audit performance of auditors in Public Accounting Firms (KAP) in Jakarta. From these findings, it is evident that knowledge has the most significant impact on auditor performance. Therefore, companies may consider providing additional training to employees, particularly informal training that enhances auditor skills, such as training related to auditing and financial examination. Offering up-to-date insights into financial knowledge and strategies for fraud detection can also be an effective step.